2022
DOI: 10.1590/1678-4324-2022220050
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Prevalence and Phenomenal Biology as Tools for Dengue Mosquito Aedes aegypti (Linnaeus) (Diptera: Culicidae) Management

Abstract: Vector monitoring is a fundamental tool for mosquito control activities and assembles information on the relative population size, species composition and advantages in dengue disease prevention. Investigations have been initiated for the exploration of relative abundance and biology of the dengue vector Aedes aegypti (Linnaeus) mosquito to provide baseline information for effective vector control and dengue prevention strategies. The studies were conducted for two years (2018)(2019) from January to December f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…The dominant trend in the population of Ae. albopictus during post-monsoon rainfall season is similar to previous finding, where seasonal conditions have a great deal of influence on the dynamics of mosquito appearance (Sarwar & Rasool, 2022). Seasonal population dynamics differed between years, and mosquito species in relation to wetland, urban and forest habitats were mainly influenced by the water level, precipitation and temperature (Vujic et al, 2010).…”
Section: Seasonal Prevalence Of Aedes Albopictussupporting
confidence: 88%
“…The dominant trend in the population of Ae. albopictus during post-monsoon rainfall season is similar to previous finding, where seasonal conditions have a great deal of influence on the dynamics of mosquito appearance (Sarwar & Rasool, 2022). Seasonal population dynamics differed between years, and mosquito species in relation to wetland, urban and forest habitats were mainly influenced by the water level, precipitation and temperature (Vujic et al, 2010).…”
Section: Seasonal Prevalence Of Aedes Albopictussupporting
confidence: 88%
“…Other studies have reported that Ae. aegypti population dynamics fluctuate depending on the season based on mean factors, such as temperature, precipitation, and breeding sites available [57][58][59][60], including studies of Ae. aegypti population dynamics in other villages of Tapachula, Chiapas [61].…”
Section: Discussionmentioning
confidence: 99%
“…Data generated from these studies were analyzed using the computer package Statistix 8.1 software, and Analysis of Variance (ANOVA) was performed at p< 0.05. Further, for the fruit flies, correlation between environmental factors and population abundance were calculated through multiple linear regression and Pearson correlation coefficient (Sarwar & Rasool 2022a;2022 b;Schober, Boer, & Schwarte, 2018).…”
Section: Discussionmentioning
confidence: 99%